Klasik Türk Mûsikîsinin Temel Sazlarından Neyde Basit Göçürme (Şed) Teknikleri / Simple Transposition Techniques in the Nay, Which is Among the Basic Instruments of Classical Turkish Music - Sevinç, Muhammet (Journal of History Culture and Art Research, 2017)
Abstract Nay (red flute), the instrument of music, is one of the main instruments of Turkish classical music and especially religious music for centuries. In this article, we will provide information about history and shape of nay and some simple techniques regarding transposing. In terms of execution, this advanced technique is important to use the instrument effectively by moving a collection of notes up or down in pitch by a constant interval. Thus we explained a few of Turkish music modes for convenience. By transposing some music notes, this study helps for music students and nay players. The article provides some examples of transposed works in its appendix as well. Öz Ney sazı, yüzyıllardır klasik Türk mûsikîsinin ve özellikle Türk din mûsikîsinin en temel çalgılarından birisi olmuştur. Bu makalede ney sazının tarihi ve yapısı hakkında bazı kısa bilgiler verilip icra açısından basit göçürme tekniklerine dair örnekler incelenmiştir. Şed veya göçürme de denilen bu teknik hemen her sazda icrada ileri seviyeye geçme ve sazı yenme açısından önem arz eder. Bu sebeple çalışmamızda, Türk mûsikîsi makamlarından birkaç tanesini başka perdelere göçürerek sazendelere kolaylık sağlamayı amaçladık. Örnek diziler ve ek bölümde verilen eserler kız neyde icra edildiğinde bolahenk nısfiye, mansur neyde icra edildiğinde ise süpürde akordu elde edilecektir.